Teacher’s Questions in Laboratory and Theory Chemistry Lessons (Sains Humanika, 2014)
Inquiry teaching is one of the teaching approaches suggested in chemistry curriculum. This mixed-method study was used to investigate teacher’s questions in chemistry’s laboratory and theory lessons. This study also determines pattern of teaching sequence(s) during chemistry lessons. Twenty three chemistry teachers who applied inquiry teaching were involved in this study. Data were collected using an observation instrument named Observation Instrument in Inquiry Teaching through Verbal Interaction and semi-structure interviews. Data were analysed using descriptive statistics. Recorded classroom observations were transcribed verbatim and analysed manually. Findings revealed that most of teacher’s questions were related to content in theory lessons. Meanwhile, in laboratory lessons, chemistry teachers emphasised almost equally both aspects; content and science process skills as required in inquiry teaching practices. In terms of pattern of teaching sequence, although IRE (initiation, response followed by evaluation) was still dominant in chemistry lessons observed, however, IR (Initiation followed by response), which supports inquiry teaching was found in this chemistry curriculum. This study showed that inquiry teaching in chemistry lessons need to be strengthened by planning it in chemistry lessons systematically in order to inculcate curiosity among the students.
Keywords: Inquiry teaching; teacher's question; science process skills; pattern of teaching sequence; verbal interaction